Aﬀective symptoms subclinical level in adolescents - B. A. Dashieva; I. S. Karaush; I. E. Kupriyanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
In the article the issues of detection and clinical signifcance of aﬀective symptoms of preclinical level in adolescence are discussed. Aﬀective symptoms of the preclinical level are frequently masked by personality or behavioral characteristics, puberty manifestations. Quite ofen such adolescents remain out of sight of specialists with a high need for adequate medical and psychological assistance. Te purpose of this study was to identify the subclinical level aﬀective symptoms in diﬀerent groups of adolescents (subthreshold depression) and to study its clinical features. Tere were examined 659 adolescents 7-17 years old. We used clinical, psychological (depression scale M. Kovak) and statistical metods. A group of adolescents with a risk of developing depression was identifed (35.7%): with a «above average» level of depression’s risk (26.6%), with a high level (7.9%) and high scores on particular scales (1.2%). Adolescents in secondary schools, compared to the pupils in correctional schools, had signifcantly higher indicators on the total score and «Negative mood» and «Angelonia» scales in the group with a high risk of depression. Te indicators of the «Interpersonal problems» scale were high in all groups of students. Adolescents from urban schools are at the greatest risk of developing depression compared to both rural adolescents and correctional school pupils. In 10.3% of the pupils, the individual signs of aﬀective disorders were identifed that signifcantly aﬀected the quality of functioning, which we regarded as persons with subthreshold depression. including 15.8% urban, 10.8% rural, and 6.3% teenagers with disabilities. Tis group needs a dynamic observation and carrying out preventive measures with the obligatory involvement of the social environment — parents and teachers.